Occupational and environmental risk factors of Leptospirosis – a case control study in a tertiary care setting in Kerala, India - REKHA RACHEL PHILIP; INDU PS; ANISH TS; SHRINIVASA BM; TEENA MARY JOY AND SUJINA CM (Health Sciences, 2013)
Context: In the recent past, the incidence of leptospirosis has been showing sudden upsurges in Kerala. Comprehensive understanding of the determinants of leptospirosis will give insight for planning effective strategies for prevention and control of this disease. Aim: The aim of the study was to identify the environmental, behavioral and occupational determinants of leptospirosis. Setting and design: A hospital based case control study was carried out in Medical College hospital at Thiruvananthapuram. Materials and Methods: The study was carried out among 52 cases of leptospirosis and 156 controls admitted in medical college hospital Thiruvananthapuram, from December 2009 to April 2010 using a structured questionnaire. Statistical analysis: Logistic regression was done to find out independent risk factors of leptospirosis. Results: Independent risk was found with working standing in water (OR= 6.53; 95% confidence interval (CI) ), 3.03,14.05), cleaning animals and their sheds (OR =5.11; 95% CI,1.51, 17.23), living close to streams (OR=2.73; 95% CI, 1.29,5.80) and male gender (2.08;95% CI,1.06,4.06). Conclusion: There are definable behavioral and environmental factors that contribute to the acquisition of leptospirosis. These risk factors are potentially correctable both at individual and the community level.